The Relationship between Lifestyle Physical Activity, Stress and Smoking with the Incidence of Hypertension in Puskesmas Padang - Indra Febra Mawandi; Ilda Melisa (Professional Evidence-based Research and Advances in Wellness and Treatment, 2024)
According to data from the World Health Organization (WHO), approximately 1.13 billion people worldwide suffer from hypertension, and less than one in five people with hypertension are well controlled (WHO, 2019). This study aims to examine the relationship between lifestyle physical activity, stress, and smoking with the incidence of hypertension in Puskesmas Padang. This study used a cross-sectional design, which aims to identify the relationship between physical activity lifestyle, stress, and smoking with the incidence of hypertension in the population visiting Puskesmas Padang. Based on the results of univariate analysis, most respondents (65.6%) reported doing physical activity. However, bivariate analysis showed that there was a significant association between physical activity lifestyle and the incidence of hypertension (p-value = 0.000). From the univariate data, only 18.8% of respondents experienced stress. However, bivariate analysis showed that stress had a significant association with the incidence of hypertension (p-value = 0.002). A total of 28.1% of respondents reported smoking. Bivariate analysis showed that smoking did not have a significant association with the incidence of hypertension (p-value = 0.447). It is important to consider other factors that may be more influential in this population. For more effective hypertension control, interventions that focus on increasing physical activity and stress management in addition to smoking reduction efforts are needed.